The effect of personal health on the formation of human capital: a metasystem approach - M.V. Sokolskaya; A.G. Madzhuga; N.S. Babieva; K.O Khvostunov; A.V. Moskvina; L.B. Abdullina; R.V. Kanbekova; R.M. Salimova; E.V. Golovneva (Intelektual Pustaka Media Utama, 2019)
In article the problem of influence of the personality’s health on formation of the human capital is considered. Authors have conducted theoretical researches of the existing knowledge of the human capital and justifications of influence of the personality’s health on its formation are given. On the basis of the carried-out analysis it is established that now the personality’s health is a significant factor of efficiency of any kind of activity and important quality of the personality, therefore, it can be considered as a factor of formation of the human capital. According to it need of determination of criteria, the indicators of health of the personality influencing formation and development of the human capital was designated.